2016
DOI: 10.5194/bg-13-4927-2016
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved particle-associated microbial respiration in the northeast Atlantic

Abstract: Abstract. Atmospheric levels of carbon dioxide are tightly linked to the depth at which sinking particulate organic carbon (POC) is remineralised in the ocean. Rapid attenuation of downward POC flux typically occurs in the upper mesopelagic (top few hundred metres of the water column), with much slower loss rates deeper in the ocean. Currently, we lack understanding of the processes that drive POC attenuation, resulting in large uncertainties in the mesopelagic carbon budget. Attempts to balance the POC supply… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 81 publications
2
40
0
Order By: Relevance
“…Due to their relatively fast sinking, POC export dominated by mesozooplankton fecal pellets generally leads to limited connectivity between sinking and suspended particle pools in the mesopelagic. Fecal pellets are indeed more resistant to remineralization compared to phytoplanktondominated particles and conferred low microbial respiration rates (Belcher et al 2016 and2016b), as they have higher densities and are surrounded by a protective membrane Duret et al…”
Section: Metazoan Components Of the Particle Fluxmentioning
confidence: 99%
“…Due to their relatively fast sinking, POC export dominated by mesozooplankton fecal pellets generally leads to limited connectivity between sinking and suspended particle pools in the mesopelagic. Fecal pellets are indeed more resistant to remineralization compared to phytoplanktondominated particles and conferred low microbial respiration rates (Belcher et al 2016 and2016b), as they have higher densities and are surrounded by a protective membrane Duret et al…”
Section: Metazoan Components Of the Particle Fluxmentioning
confidence: 99%
“…Originally, MSCs were designed to capture large rare particles with minimal disturbance from turbulence [Lampitt et al, 1993] and often the main focus of MSC sampling is still fast-sinking particles. The carbon content of fast-sinking particles collected from MSCs has, until recently [Belcher et al, 2016b], always been calculated using imaging and Alldredge [1998] conversion factors. However, Bishop et al [2016] recently reported that Alldredge [1998] conversion factors underestimate the carbon content of aggregates considerably.…”
Section: 1002/2017gb005638mentioning
confidence: 99%
“…However, Bishop et al [2016] recently reported that Alldredge [1998] conversion factors underestimate the carbon content of aggregates considerably. In the future we would recommend measuring POC of the fast-sinking particles directly as in Belcher et al [2016b] but as this study is a retrospective data collation, using conversion factors is unavoidable. To investigate whether conversion factors affected the results found in the Southern Ocean, we also calculate the fastsinking POC fluxes using two conversion factors for FP [Alldredge, 1998;Manno et al, 2015] which demonstrated differences in magnitude but minimal change in observed trends (see section 3.4).…”
Section: 1002/2017gb005638mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a fraction of PP leaves the upper ocean, known as the export efficiency (export flux/PP). The export efficiency is affected by multiple factors such as phytoplankton community structure (which may affect formation of aggregates or sinking by ballasting; Buesseler, 1998;Boyd & Newton, 1999;Francois et al, 2002), zooplankton (which package phytoplankton into fast-sinking fecal pellets or may transfer carbon directly to depth via diel vertical migration; Cavan et al, 2015;Dagg et al, 2014;Steinberg et al, 2002), and bacterial remineralization (Belcher et al, 2016;Buchan et al, 2014;Buesseler et al, 2007;Le Moigne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%